Savage vs. Anscombe-Aumann: an experimental investigation of ambiguity frameworks - Oechssler, Joerg; Roomets, Alex (Discussion paper series, 2019)
The Savage and the Anscombe-Aumann frameworks are the two most popular approaches used when modeling ambiguity. The former is more flexible, but the latter is often preferred for its simplicity. We conduct an experiment where subjects place bets on the joint outcome of an ambiguous urn and a fair coin. We document that more than a third of our subjects make choices that are incompatible with Anscombe-Aumann for any preferences, while the Savage framework is flexible enough to accountfor subjects' behaviors.
Keywords: Graue Literatur